Formação continuada em tempos e espaços de serviço na perspectiva da práxis Benincaniana - Santos, Roselange dos (2023)
The present dissertation, entitled Continuing education in times and spaces of service from the perspective of Benincan praxis, developed in the line of Educational Policies of PPGEDU/UPF, analyzed an experience of continuing teacher education in the city of Soledade/RS. The research was developed under the Program for Continuing Education of Education Workers-PROFORMA, in the period from 2013 to 2022. In the context of this temporal and thematic delimitation, the following research problem was adopted: How has the praxis perspective, with special reference to Elli Benincá's production, been guiding the experience of continuing education in the PROFORMA Program, what are the advances made and what are the obstacles that hinder further progress? The general objective was to analyze the continuing education in the municipal network of Soledade/RS, the theoretical assumptions that support it, the participation of educators, the advances and challenges posed to it. The specific objectives were: (a) to historicize this continuing education experience, its challenges, limits and resistances; (b) to analyze the theoretical principles that sustain the program, among which are dialogue and praxis; (c) to delve into the advances and challenges of continuing education in the Soledade educational system. The dissertation was based on a bibliographic and documental research with fragments of memories, and is structured in four chapters, the first one being the introduction and the fourth the conclusion. In the second chapter, the historical trajectory of the continuing education program in Soledade/RS is reconstructed, since its beginnings in 2009, the collective and systematic involvement of teachers from 2013, as well as the tensions, resistance and advances. The concept of continuing education in different regulations is also discussed. The third chapter analyzes the theoretical assumptions that underlie the experience of continuing education studied, especially the concepts of dialogue and praxis, with Elli Benincá as reference and Paulo Freire's contributions. This chapter aims to deepen the understanding of continuing education anchored in a transformative praxis and the re-signification of pedagogical common sense from the tensions between initial training and the practices in everyday school life. The fourth chapter discusses continuing education in school times and spaces with emphasis on the collective and the dialogical-participatory praxis. This training model aims to ensure educational public policies that prioritize critical reflection in a context guided by neoliberal, competitive, and individualistic rationality. As a counterpoint, continuing education is understood as a possibility for overcoming simplistic and reductionist educational discourses, as well as the advances of the private sector over the public sector, especially in the continuing education of education professionals. Finally, we conclude that continuing education, from a praxis perspective, demands a lot of effort, patience, public investment, and the ability to reflect the challenges emerging from the practices, aiming at a critical and emancipating education. The experience of the Soledade/RS public education system shows that a quality continuing teacher education needs to be anchored theoretically and pedagogically in critical-dialogical traditions and adopt a perspective of continuity.